The State of Speech : Rhetoric and Political Thought in Ancient Rome - Connolly, Joy, 1970- (Book collections on Project MUSE., 2007)
Rhetorical theory, the core of Roman education, taught rules of public speaking that are still influential today. But Roman rhetoric has long been regarded as having little important to say about political ideas. The State of Speech presents a forceful challenge to this view. The first book to read Roman rhetorical writing as a mode of political thought, it focuses on Rome's greatest practitioner and theorist of public speech, Cicero.